Analysis of the first test-event of Santa Catarina, Brazil, no contexto da COVID-19 pandemic em julho de 2021: experience report - Schuelter-Trevisol, Fabiana (2022)
This study aimed to describe the management and results of the test event to make distancing measures more flexible in Santa Catarina, Brazil. This is an experience report that described results of the test-event, carried out in July 2021 and for which the participants underwent the real-time polymerase chain reaction diagnostic test 72-48 hours before, being monitored for 15 days. The outcomes analyzed were SARS-Cov-2 infection up to 14 days after the event and presence of symptoms. Among 313 participants, the mean age was 45.1 years and 54.3% were female. In the monitoring, 7.7% (24) of the contacted participants reported symptoms compatible with infection, but of the 240 who attended for post-event testing, none of the results detected the presence of the virus. There were no post-event COVID-19 cases reported. It is suggested that other test-events be carried out to evaluate the recommendations indicated.